Analisis Manajemen Stok Jagung di Perum BULOG Divisi Regional Provinsi Jawa Timur - Debby Diandra; Titik Ekowati; Hery Setiyawan (Fakultas Ekonomi Universitas Negeri Jakarta, 2017)
Corn is a staple food and main ingredient for feed manufacturing in Indonesia. In accordance with Ministry of Agilculture Regulation (Permentan) No. 57 on corn import regulation 2015 Signed, Indonesian Bureau of Logistics (Perum BULOG) is the only company that has permission to import corn. The purposes of this research are to 1) analyze the optimization of the corn supply in Indonesian Bureau of Logistic East Java Regional Division; 2) analyze the cost efficiency of corn supply In Indonesian Bureau of Logistics (Perum BULOG) East Java Regional Division; 3) analyze the projection of economic corn total order in Indonesian Bureau of Logistics (Perum BULOG) East Java Regional Division from the Third Quarter of 2017—the First Quarter of 2019. This research employs the method of case study. The first purpose is analyzed by implementing economic order quantity (EOQ) method. The second purpose is analyzed by exercising the TIC and cost efficiency formula. The third purpose is analyzed by calculating the least square trend. The optimization of corn supply of Indonesian Bureau of Logistic East Java Regional Division is not optimum. The cost efficiency of corn supply of Indonesian Bureau of Logistic East Java Regional Division is not efficient. The projection of EOQ trend in the Third Quarter of 2017—the First Quarter of 2019 tends to decline. Keywords: BULOG; corn; cost efficiency; economic order quantity; least square trend